Cost-effective analysis and budget comparison of laparoscopic radical prostatectomy and robotic-assisted radical prostatectomy for prostate cancer treatment in a health insurance system in Thailand - Komvuttikarn, Keeree; Sangkum, Premsant; Kongchareonsombat, Wisoot; Kijvikai, Kittinut (Insight Urology, 2021)
Objectives: To compare the total medical cost and post-operative quality of life between laparoscopic radical prostatectomy (LRP) and robotic-assisted laparoscopic radical prostatectomy (RALP) and to discuss the cost differences of each approach. Materials and Methods: Data were retrospectively reviewed from patients diagnosed with prostate cancer and who underwent LRP (n=68) or RALP (n=104) during a 36-month period. The prostate cancers of all patients were classified as low, intermediate, or high risk. Patient variables, inpatient hospital charges, outpatient total medical costs within 24 months and post-operative quality of life were compared. Results: The baseline patient characteristics were similar between each group. Rates of positive margins and the need for further cancer treatment were correlated with the burden of disease (highest in the high risk group). The RALP inpatient hospital charges were higher in all risk groups. However, the mean total outpatient hospital charges were comparable. The RALP group demonstrated a trend towards better sexual-related quality of life in all risk groups. However, urinary incontinence, urinary-related, bowel-related, vitality-related quality of life were not significantly different between LRP and RALP. Conclusion: From the payer’s perspective, RALP costs are higher than LRP costs. The clinical and quality of life benefits associated with RALP may not convert into a net savings of total medical costs within 24 months after surgery.